Youth crime and education expansion - Stephen Machin; Olivier Marie; Sunčica Vujić (Institute for the Study of Labor (IZA), 2012)
We present new evidence on the causal impact of education on crime, by considering a large expansion of the UK post-compulsory education system that occurred in the late 1980s and early 1990s. The education expansion raised education levels across the whole education distribution and, in particular for our analysis, at the bottom end enabling us to develop an instrumental variable strategy to study the crime-education relationship. At the same time as the education expansion, youth crime fell, revealing a significant cross-cohort relationship between crime and education. The causal crime reducing effect of education is estimated to be negative and significant, and considerably bigger in (absolute) magnitude than ordinary least squares estimates. The education boost also significantly impacted other productivity related economic variables (qualification attainment and wages), demonstrating that the incapacitation effect of additional time spent in school is not the sole driver of the results.
Keywords: I2; K42; 330; youth crime; education expansion; Jugendkriminalität; Bildung; Großbritannien